The Urgency of Renewing the Theory of Punishment in the Formation of National Criminal Law Policy - Wakhidatul Mubarokah; Ali Masyhar Mursyid; Cahya Wulandari (Pusat Riset dan Inovasi Nasional, 2025)
The formulation of the National Criminal Code through Law Number 1 of 2023 highlights the importance of reforming sentencing theory to anticipate legal and social developments in Indonesia. This study adopts a normative qualitative approach, taking into account the evolution of sentencing paradigms. The findings reveal that the sentencing theory in the new Criminal Code has shifted from a retributive model to an integrative model. It combines restorative justice, absolute, and relative theories. Sentencing today is not solely aimed at punishment, but also at restoring social relations and protecting human rights. The introduction of more diverse types of punishment, the recognition of corporations as legal subjects, and the establishment of sentencing standards as judicial guidelines reflect this reform. In conclusion, a more humanistic and responsive national criminal law policy depends on the development of sentencing theory.